Perencanaan Komunikasi Event Ruang Visi Nusantara Bengkulu (Studi Pada Event “Linimasa Masanya Segala Lini”) - Sari, Melinda; Muwarni, Anis Endang Sri; Putra, Dilmai (Universitas Dehasen Bengkulu, 2025)
An event organizer is a business that operates in the field of professional service provision. Event organizers assist with personal events such as weddings and birthdays, as well as other events. The type of research used by the researchers is descriptive qualitative. Data collection was carried out using observation techniques, interviews, and documentation techniques. The informants in this study consisted of several parties from RVN Management, including the Head of the Public Relations and Information Division, the Marketing Division, and the Event Manager. Based on field data, in the planning and implementation process of the concert